(Dis)figurations : discourse/critique/ethics - Angus, Ian (Phronesis (London, England), 2000)
There has been, over the last decades, a deep crisis in the models which, for a long time, have been central metaphors governing thought and research in the social sciences. The main symptom in this paradigmatic shift has been the increasing centrality of the "discourse" approach in social theory. It is Ian Angus's aim here to explore thoroughly the philosophical implications of this shift. He does so by combining serious philosophical reflection with an analysis of the media, which draws on both the phenomenological tradition and the political concerns of the Frankfurt School, post-Marxism and radical democracy. Ranging over the work of Heidegger and Gramsci, this philosophical exploration is not carried out by Angus as a purely analytical enterprise, but as a comprehensive attempt at rethinking the whole project of a critical philosophy.